INFLUENCE OF SPACING ON SELF-THINNING OF A MONOCLONAL STAND OF Eucalyptus saligna Smith - Schneider, Paulo Renato (2015)
http://dx.doi.org/10.5902/1980509817468In the present study the effect of initial spacing on relationship between the density of trees per hectare and the average diameter in monoclonal stands of Eucalyptus saligna were investigated. The data used were collected from full stocked stands and highly stored annually, monitored until 18 years old using permanent plots. For that, the density model of trees per hectare by diameter was tested and the self-thinning model of Tang was indicated as the most accurate one and provided great performance statistics, with a coefficient of determination equal to 0.85, lower standard error equal to 0.1026, low coefficient of variation equal to 1.39%, a minimal tendency equal to -0.0534 and high-efficiency equal to 0.3903. The self-thinning occurs in a diameter directly proportional to the initial density of trees per hectare of plantation. As great is the initial spacing greater is the mean diameter in the moment of initiation of self-thinning of the population. The slope of the equation of density and diameter was equal to 1.0124 diverging from the value indicated for forest species in the law of self-thinning.